Consolidation of cobalt nanorods: A new route for rare-earth free nanostructured permanent magnets. (15th February 2018) - Ener, Semih; Anagnostopoulou, Evangelia; Dirba, Imants; Lacroix, Lise-Marie; Ott, Frédéric; Blon, Thomas; Piquemal, Jean-Yves; Skokov, Konstantin P.; Gutfleisch, Oliver; Viau, Guillaume
Abstract: Rare-earth free permanent magnets were produced by consolidation of cobalt nanorods synthesized by the polyol process exhibiting a mean diameter in the range 10–30 nm. Compactions of magnetically prealigned rod assemblies at various pressures and temperatures were carried out to make dense materials. Bulk magnets exhibiting a very good mechanical strength and an energy product as high as 65 kJ m −3 were obtained. The best results were obtained when the compaction conditions were soft enough to preserve the morphology and alignment of the rods in the final material, as revealed by X-ray diffraction and neutron scattering. For the first time the bottom-up approach is convincingly reported to produce bulk magnets without the addition of any matrix, the obtained nanostructured materials exhibit coercivity much higher than the AlNiCo magnets and can fill the performance "gap" between hexaferrites and rare-earth based magnets. Graphical abstract: Image 1